The Effectiveness of Ethnomathematics-Based Learning on Students’ Mathematical Representation in Indonesia: A Meta-Analysis Study - Pratama, Ryan Angga; Afriani, Rika (Journal of Teaching and Learning, 2026)
This meta-analysis aims to examine the extent to which ethnomathematics-based learning improves students' mathematical representation abilities and to identify moderator variables that influence its effectiveness. The results of the literature review in the Google Scholar database yielded 11 studies that met the inclusion criteria. Furthermore, the effect sizes were combined according to the Random Effects Model (REM). Data analysis was performed using CMA v3 and R Studio (Meta Package). The results of the study showed that ethnomathematics learning had a significant effect, with an effect size of . This value indicates that the ethnomathematics approach has a strong positive impact on students' mathematical representation abilities. In addition, the effectiveness of ethnomathematics-based learning is influenced by several moderator variables, including education level, cultural background, independent variables, experimental design, and type of publication. However, other variables such as duration of learning, subject matter, and number of students were not proven to moderate the relationship between ethnomathematics-based learning and students’ mathematical representation. It is also hoped that the results of this study can be the basis for policy making for stakeholders in the world of education (in this case teachers/schools/education offices) so that the quality of mathematics learning in the classroom can be more optimal.